EFFECTIVENESS OF APPLYING BIM BASED COST ESTIMATION IN DEVELOPMENT OF THE SYAMSUDIN NOOR AIRPORT PROJECT BANJARMASIN - Khatimi, Husnul; Fardian, Muhammad Reza; Sari, Yuslena (ASTONJADRO, 2021)
Development of The Syamsudin Noor Airport Project in Banjarmasin is one of the largest projects in Banjarmasin, South Kalimantan. This project applied BIM-based cost estimation on a steel roof structure. However, the cost estimation for this steel roof structure is applied conventionally. The BIM-based cost estimation could have been applied in collaborating a building information becomes unity in one model. This research will raise the issue of applying BIM-based cost estimation at The Syamsudin Noor Airport Project to find out the effectiveness calculation of cost estimation conventionally and BIM-based cost estimation. The report result by 3D modeling of Tekla is quantity take-offs using as a data for processing the cost analysis conventionally. Whereas the 3D model made by Tekla will be exported to Revit through the interoperability of IFC or application of extention of Tekla warehouse that is "Export to Revit Geometry” for the processing the BIM-based cost estimation analysis. The unit price for the cost calculation is acquired by list price (AHSP or subcontractor value). The result of these both cost calculation, there are large enough difference in cost of these both calculations. Difference of conventional calculations and BIM-based cost estimation using Revit worth Rp 3,690,741,474 - Rp 5,047,206,780 with a percentage of 14% - 20%. Cause of these large enough differences in cost due to the model exported is only 90% succeeded. It happened due to difference thing in the mapping of object profile and difference in shape BREP geometry conditions.